Experimental Research on Seismic Performance of Masonry-Infilled RC Frames Retrofitted by Using Fabric-Reinforced Cementitious Matrix Under In-Plane Cyclic Loading - Wang, Fayu (My University, 2023)
Fabric-reinforced cementitious matrix (FRCM) composites, also known as textile-reinforced mortars (TRMs), represent a new advancement in structural repair and reinforcement technology. Aiming to improve the energy efficiency and seismic performance of existing buildings, this research focused on the development of an FRCM system in combination with phase change materials (PCMs) and extruded polystyrene sheets (XPS) to achieve adequate mechanical and thermal properties for reinforced concrete (RC) and masonry structures. Accordingly, the in-plane behaviour of five FRCM-strengthened RC frames with hollow-brick wall infill was tested under cyclic loading to investigate the improvement in earthquake resistance. The system was comprehensively evaluated by calculating hysteresis curves; comparing the lateral stiffness, ductility, and energy dissipation capacity; measuring the deformations of the specimens; and analysing the failure modes mechanically. Finally, it was proved that this novel integrated approach could significantly enhance the mechanical and seismic performance of masonry-infilled RC frames.
Keywords: Fabric-reinforced cementitious matrix; Failure mode analysis; In-plane behaviour; Masonry walls; Phase change materials; RC frames; Seismic performance; Structural deformation; Thermal insulation